Propuesta de diseño de un sistema para la recolección del material particulado (área de secamiento de arroz empresa arrocera Agrocom SAS - Villavicencio) (2021)
This research proposes the design proposal of a particulate material collection system in the drying area of the Agrocom SAS rice plant, located at km 5 via López - Villavicencio port, in the city of Villavicencio, department of Meta. It is based on the need to reduce particulate matter during the green paddy drying process, which affects workers, the nearby community, machinery and equipment of the company, it is posed to the company a collection system, selecting the components according to the needs of the production process. The system consists of four important parts which work together to achieve effective collection of the contaminant; It begins with the capture, it is the entry point of the air flow that contains the particulate material to the system, it is located in front of the pollutant source and it is usually done with an element called a hood; then the conduction, which is the section of pipe or ducts that conduct the air flow with the load of particulate material and cap through the hood; Almost at the end is the fan being the element used to mobilize the air flow through the ducts, providing the energy necessary for the charge of particulate material to reach the purification equipment and finally the air purification equipment, which is the device in charge. of the separation of particles suspended in the air flow.